From Aspiration to Action? The Impact of Germany's 2015 Dublin III Suspension on Migration Intentions in Arab Countries - Andreas B. Vortisch; Evangelos Paschalidis; Michel Beine; Michel Bierlaire (CESifo GmbH, 2025)
On 5 September 2015, the German government suspended the EU's Dublin III regulations, allowing all asylum seekers to apply for asylum in Germany. This policy change motivated more than one million people, especially Syrians, Afghans, and Iraqis, to enter the country. This study examines the impact of this policy change on migration aspirations and actions in 11 Arab countries, assessing whether it increased migration pressure toward Germany. We find that while the policy raised migration aspirations, it did not significantly affect concrete migration plans and therefore immigration pressures. Instead, age and personal networks abroad play more decisive roles in shaping such plans. Additionally, territorial control by IS in certain regions served as a distinct push factor. We also analyze migration preparations and find that age and networks abroad remain key determinants. Our results also suggest that the policy may have altered the composition of those planning to migrate.
Keywords: C25; F22; J61; 330; migration aspirations; migration plans; immigration policies; refugees